Samoocena sytuacji jednostek samorządu terytorialnego zawarta w strategiach rozwoju gmin - Sekuła, Alicja (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article presents the results of the research on the subject of the communes situation from the point of view of territorial units. The basis of the conclusions drawn was SWOT analysis presented in local development strategies. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 314-324